THE STUDY OF PROGRAM AND ROLES OF NATIONAL CONSUMER PROTECTION AGENCY USING QUALITATIVE AND QUANTITATIVE APPROACHES - Mutia Rahmah; Megawati Simanjuntak; Anggi Mayang Sari; Irni Rahmayani Johan (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
The National Consumer Protection Agency (BPKN) was established to fulfill consumer protection needs in accordance with its duties. This study aimed to identify the role and performance of BPKN. The research design used was a mixed method. A total of 224 respondents were selected for the online survey using voluntary sampling techniques with the criteria of Indonesian citizens, men, and/or women aged 18-65 years, and in-depth interviews with the Chairman of the Research and Development Commission of BPKN. Data analysis was performed using Microsoft Excel 2013 and SPSS version 25.0. The result of this research is that more than half of consumers know about the functions and duties of the BPKN. However, the number of respondents who knew about BPKN programs was still low. The role of the BPKN in providing suggestions and recommendations to the government is considered insufficient based on the number of suggestions and recommendations issued each year. On the other hand, BPKN has succeeded in creating new innovations in how consumers complain during the COVID-19 pandemic, namely, by making online complaints. BPKN should be able to create more activities aimed at introducing BPKNs among Indonesians.